CRIMINAL RESPONSIBILITY OF PERPETRATORS OF ASSAULT DUE TO SOCIAL CONFLICT IN KAMPAR REGENCY - Boby Putra Ramadhan Sebayang; Irawan Harahap; Miftahul Haq (JILPR Journal Indonesia Law and Policy Review, 2026)
The purpose of this study is to analyze the criminal liability of perpetrators of assault due to social conflict in Kampar Regency, to analyze the obstacles to criminal liability of perpetrators of assault due to social conflict in Kampar Regency, and to analyze efforts to overcome these obstacles. The method used is sociological legal research. Based on the research results, it is known that Criminal Liability of Perpetrators of Assault Due to Social Conflict in Kampar Regency can be imposed as long as it can be proven that there was an unlawful act and the perpetrator was at fault. However, in practice, proving the element of fault becomes more complex because the incident occurred on a mass scale and was influenced by the conflict situation. Criminal accountability fundamentally adheres to the basic principles of criminal law, namely the existence of fault, the capacity to take responsibility, and the absence of justification or excuse. In the context of Law Number 1 of 2023 concerning the National Criminal Code, assault remains a criminal act for which individual responsibility must be met, even when occurring in situations of social conflict involving many people. Various obstacles exist in the criminal accountability process, including the difficulty of obtaining evidence and the lack of witnesses, the strong culture of family resolution in society, the limited number of law enforcement personnel, and the influence of mass emotions and group solidarity. These obstacles prevent the law enforcement process from always being effective and optimal. Efforts to overcome these obstacles require various measures, such as strengthening the evidentiary system and witness protection, optimizing the selective application of restorative justice, increasing the capacity of law enforcement officers, and increasing public education and legal awareness. These efforts are expected to strengthen the effectiveness of law enforcement and create a balance between justice, legal certainty, and expediency.